The Two-Way Influencing Mechanism Between Corporate Governance Structure and Equity Market Performance in China’s Health and Tourism Industry - Gu , Miaomiao; Leelapattana, Winitra; Tsai , Chin-Fa; Sitthikun, Suthira (International Journal of Multidisciplinary in Management and Tourism, 2024)
This article aimed to study the interactive relationship between corporate governance structure and equity market performance. The China Securities Regulatory Commission (CSRC) classifies listed companies in the A-share market into different industries, each of which represents a different field of economic activity. One of these industries is the health and tourism industry. The sample for this study includes seven Chinese listed companies in the health and tourism industry. Data were collected through interviews and analysed qualitatively. The research results are as follows: 1. A strong governance structure can effectively reduce investors’ expected risk for stock investments. This risk reduction can be attributed to several key elements of corporate governance, including transparent decision-making processes, clear accountability, and effective risk management mechanisms. 2. Empirical evidence further confirms the direct link between the quality of corporate governance and the financial health of firms. Firms with sound governance structures not only enhance their attractiveness to investors but may also increase stock returns. 3. The empirical study of Chinese listed companies in the health and tourism industry specifically points out that good corporate governance is not only a determining factor in achieving financial success, but that it can indeed lead to positive results. The findings emphasize the importance of prioritizing and continuously improving corporate governance, which is beneficial for both the company and its stakeholders. By ensuring a sound governance structure, companies can better manage risks, increase transparency, enhance market trust and ultimately achieve long-term financial soundness and growth.